First observation of Bs0→J/ψf0(980) decays - Aaij, Roel; Bachmann, Sebastian; Deissenroth, Marc; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Holubyev, Kostya; Krocker, Georg Alexander; Linn, Christian; Marks, Jörg; Meißner, Marco; Uwer, Ulrich; et al. (Physics letters, 2011)
Using data collected with the LHCb detector in proton-proton collisions at a centre-of-mass energy of 7 TeV, the hadronic decay Bs0→J/ψf0(980) is observed. This CP eigenstate mode could be used to measure mixing-induced CP violation in the Bs0 system. Using a fit to the π+π− mass spectrum with interfering resonances gives Rf0/ϕ≡Γ(Bs0→J/ψf0,f0→π+π−)Γ(Bs0→J/ψϕ,ϕ→K+K−)=0.252−0.032−0.033+0.046+0.027. In the interval ±90 MeV around 980 MeV, corresponding to approximately two full f0 widths we also find R′≡Γ(Bs0→J/ψπ+π−,|m(π+π−)−980 MeV|<90 MeV)Γ(Bs0→J/ψϕ,ϕ→K+K−)=0.162±0.022±0.016, where in both cases the uncertainties are statistical and systematic, respectively.
*LHCb Collaboration: R. Aaij, S. Bachmann, M. Deissenroth, F. Eisele, C. Färber, S. Hansmann-Menzemer, K. Holubyev, G. Krocker, C. Linn, J. Marks, M. Meissner, U. Uwer, S. Wandernoth, D. Wiedner, A. Zhelezov [und 532 weitere Personen]
Im Titel ist der Buchstabe s tiefgestellt
Im Titel ist die Zahl 0 im Ausdruck "Bs0" hochgestellt sowie im Ausdruck "J/ψf0(980)" tiefgestellt
Gesehen am 16.02.2022